Experience of Glucose Control: A Qualitative Study of Diabetes Mellitus Type 2 Patients - Purwanto, Cucuk Rahmadi; F, Fifi Linda; Nasir, Abdul; Okviasanti, Fanni; Kusnanto, Kusnanto (International Journal of Psychosocial Rehabilitation, 2020)
The identification of various phenomena related t type 2 diabetes mellitus, especially concerning the recognition of the signs, symptoms and blood glucose levels that affect emotional responses, is important for diabetics to use as a basis for determining the action strategy that is to be performed. This was identified in order to maintain blood glucose control during diabetes mellitus. This study aims to explore the efforts to control blood glucose to achieve an improved well-being among people with diabetes mellitus. This research used a qualitative method through a phenomenological approach and a purposive sampling technique. The data analysis used the Interpretative Phenomenology Analysis approach through in-depth interviews, observations and assistance from the patient’s note files. The population involved 15 participants with diabetes mellitus type 2. The study produced the theme `maintaining personal well-being’. Three sub-themes were identified: (1) trying to find accurate information, (2) feeling in a traumatic event and (3) managing effective coping strategies. The efforts undertaken present specific challenges related to maintaining and improving personal well-being especially when dealing with situations of increasing blood glucose during diabetes mellitus. These challenges are confronted so as to improve their healthy behavior through efforts to maintain their diet, exercise, stress management and blood glucose. This includes taking their medication regularly and controlling the patient's coping mechanism.